Development of Interactive Teaching Materials Based on Moodle, Automation of Facilities and Infrastructure Management - Rotua SP Simanullang; Ellys Siregar; Gartima Sitanggang; Aurora Elise Putriku (Outline Journal of Education, 2025)
The availability of interactive teaching materials to support students' understanding of the automation of infrastructure management is needed. For this reason, the development of interactive teaching materials based on Moodle was carried out to be used in the teaching and learning process in the classroom. This research is a R&D (Research and Development) development research referring to the ADDIE development model with stages of analysis, design, development, implementation and evaluation. The research subjects were one media expert and one material expert, with 3 students for individual testing, 12 students for limited testing and 30 students for field testing consisting of 1 class. The results of the study showed (1) validation from media experts 88.33% in the very feasible category and the results of validation from material experts 84.33% in the feasible category. (2) The results of individual trials were 83.99% and the results of limited trials were 85.44%, which means that the interactive teaching materials based on Moodle that were developed were feasible and could be used for students with different abilities. (3) The results of the N-gain test in the class using interactive teaching materials based on Moodle that were developed were 0.77 in the high category, meaning that the interactive teaching materials based on Moodle that were developed were proven to be effective in improving student learning outcomes in the automation of infrastructure management course.